Laminate, and plastic container

The laminate structure with amorphous cyclic olefin resin and polyethylene/polypropylene layers addresses drug adsorption and permeation issues, maintaining transparency and impact resistance for pharmaceutical containers, ensuring storage stability and regulatory compliance.

JP2024177492AActive Publication Date: 2024-12-19ZACROS CORP

Patent Information

Application Number
JP2024175736
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-02-05
Filing Date
2024-10-07
Publication Date
2024-12-19
Estimated Expiration
2039-02-05

AI Technical Summary

Technical Problem

Existing plastic containers for pharmaceuticals face issues with drug adsorption, permeation, impact resistance, and transparency loss during sterilization, which affect storage stability and compliance with regulatory standards.

Method used

A laminate structure comprising a first resin layer with amorphous cyclic olefin resin and a second resin layer with polyethylene or polypropylene, optionally with an adhesive resin layer, enhances interlayer adhesion and maintains transparency and impact resistance, using elastomers to improve flexibility and strength.

Benefits of technology

The laminate provides excellent storage stability, maintains transparency after sterilization, and offers improved impact resistance, ensuring compliance with regulatory standards for pharmaceutical containers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177492000001_ABST
    Figure 2024177492000001_ABST
Patent Text Reader

Abstract

To provide a laminate and a plastic container that hardly cause a decrease in transparency even after sterilization treatment and breaking under impacts such as dropping, exhibit suitable strength as a storage container, and offer superior storage stability for ingredients such as pharmaceuticals stored therein.SOLUTION: A laminate is composed of at least two layers, the layers including a first resin layer 11 that includes an amorphous cyclic-olefin-based resin configured from an olefin monomer component having a cyclic hydrocarbon skeleton, and a second resin layer 12 that has polyethylene, polypropylene or ethylene α-olefin copolymer as a main component, wherein the first resin layer 11 contains a thermoplastic elastomer in a proportion of 10 mass% or less and is an innermost layer in contact with the contents. An adhesive layer or an anchor agent layer may be interposed between each layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and a container. [Background technology]

[0002] In recent years, soft bag formulations have been developed for intravenous infusion, in which drugs to be injected are diluted and prepared in advance and packed into flexible containers (plastic containers) made of plastic, etc. These soft bag formulations are considered useful because they are convenient and quick to use, and because they reduce the risk of breakage and are easier to dispose of than glass bottles or ampoules. This application claims priority based on Japanese Patent Application No. 2018-018232, filed on February 5, 2018, the contents of which are incorporated herein by reference.

[0003] However, films made of ordinary polyolefin resins (hereinafter sometimes referred to as "PO resins") such as polyethylene (hereinafter sometimes referred to as "PE") and polypropylene (hereinafter sometimes referred to as "PP"), and resins commonly used as materials for pharmaceutical containers such as polyvinyl chloride, adsorb or permeate some drugs, including radical scavenging preparations. As a result, the active ingredients of the drug solution are adsorbed to the plastic container, or the drug solution interacts with additives and low molecular weight components contained in the resin film that makes up the plastic container, which has been an issue in developing soft bag formulations.

[0004] Therefore, it has been proposed to use cyclic olefin resins as resins that have barrier (shielding) properties and suppress the adsorption and permeation of drugs and the like into plastic containers. Cyclic olefin resins have an alicyclic hydrocarbon structure in the molecular skeleton, which makes them bulky and restricts the movement of the molecular chain, making it difficult for molecules to be absorbed or permeated, and they are known to exhibit excellent storage stability due to their small interaction with the above-mentioned additives and drug ingredients.

[0005] For example, Patent Document 1 describes that an infusion bag having an outer layer (surface layer) made of PP, an innermost layer made of cyclic olefin resin, and an intermediate layer made of PP between the two layers is suitable as a container for storing "Edaravone". Although a container having such a configuration has sufficient storage stability for the preparation, the cyclic olefin resin is hard and brittle, and when the container is accidentally dropped or subjected to an impact, it has a problem in impact resistance, such as partial peeling of the seal or destruction such as pinholes, which leads to liquid leakage.

[0006] Cycloolefin resins have the problem that they are prone to producing gels or fish eyes due to aggregation of components contained in the resin, or defects (in the sense of kneaded foreign matter, etc.) due to oxidation or carbonization during film formation or molding. To compensate for these shortcomings, Patent Documents 2 and 3 propose a means of blending a certain ratio of polyethylene, polypropylene, or ethylene-α-olefin copolymer (olefin resin) with the cyclic olefin resin.

[0007] This technology improves processability, but there is a problem in that the transparency of the container is significantly reduced by the steam sterilization operation carried out after filling with medicines, etc. This problem is undesirable because it becomes an obstacle when inspecting the quality of the contents by visual inspection or camera during the manufacturing process of pharmaceuticals, etc., and there is a concern that it may deviate from the transparency standard stipulated in 7.02 Testing Method for Plastic Pharmaceutical Containers of the 17th Revised Edition of the Japanese Pharmacopoeia.

[0008] Furthermore, when the weight of the contents is heavy, the ratio of the olefin-based resin to be blended must be increased in order to impart a sufficient level of impact resistance, but this increases the molecular mobility of the barrier layer, which may result in a decrease in the concentration of the components of the contents and other problems that may result in insufficient storage stability, which is what is required for the container to function.

[0009] As described above, for pharmaceuticals and other products for which drug adsorption is likely to occur in plastics, a plastic container that has sufficient transparency and physical properties while also providing excellent storage stability for the drug solution components has not yet been developed, and there is a demand for such a container to be developed. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2016-22092 A [Patent Document 2] JP 2012-86876 A [Patent Document 3] Special Publication No. 2005-525952 Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a laminate and a plastic container which are resistant to a decrease in transparency even when subjected to sterilization treatment, are resistant to breakage due to impacts such as being dropped, have appropriate strength as a storage container, and have excellent storage stability of the ingredients of the contained contents, such as pharmaceuticals. [Means for solving the problem]

[0012] In order to solve the above-mentioned problems, the present invention provides a laminate consisting of at least two layers including a first resin layer containing an amorphous cyclic olefin-based resin composed of an olefin monomer component having a cyclic hydrocarbon skeleton, and a second resin layer containing polyethylene, polypropylene or an ethylene-α-olefin copolymer as a main component, wherein the first resin layer contains an elastomer in a proportion of 10 mass % or less.

[0013] The elastomer may be a thermoplastic elastomer. The thermoplastic elastomer may be selected from one or more of an olefin-based thermoplastic elastomer and a styrene-based thermoplastic elastomer. The elastomer may be contained in the first resin layer in a proportion of 0.05 to 10% by mass.

[0014] The present invention also provides a plastic container, characterized in that it has a storage section for storing contents, and an opening for discharging the contents, the storage section being arranged so that the above-mentioned laminate is overlapped facing each other.

[0015] The contents may be a medicine. The pharmaceutical agent may be an aqueous solution containing the pyrazolone derivative, edaravone, or a pharma- ceutically acceptable salt thereof. The plastic container may be an infusion bag or a blow molded container. Effect of the Invention

[0016] According to the present invention, it is possible to provide a laminate and a plastic container which have excellent interlayer adhesive strength and heat seal strength, are resistant to loss of transparency even during high-temperature sterilization treatment and the like, are resistant to breakage due to impacts such as being dropped, have appropriate strength as a storage container, and have excellent storage stability of the ingredients of the contained contents, such as pharmaceuticals. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a cross-sectional view showing a laminate according to the first embodiment. [Diagram 2] FIG. 4 is a cross-sectional view showing a laminate according to a second embodiment. [Diagram 3] FIG. 11 is a cross-sectional view showing a laminate according to a third embodiment. [Figure 4] FIG. 11 is a cross-sectional view showing a laminate according to a fourth embodiment. [Diagram 5] FIG. 1 is a side view showing an example of a plastic container of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, the present invention will be described based on preferred embodiments. The laminate of the present embodiment is a laminate consisting of at least two layers including a first resin layer containing an amorphous cyclic olefin-based resin composed of an olefin monomer component having a cyclic hydrocarbon skeleton, and a second resin layer containing polyethylene, polypropylene or an ethylene-α-olefin copolymer as a main component, and is characterized in that the first resin layer contains an elastomer in a proportion of 10 mass% or less.

[0019] The laminate 10 shown in Fig. 1 has a two-layer structure in which a second resin layer 12 is disposed on one side of a first resin layer 11. The laminate 20 shown in Fig. 2 has a three-layer structure in which a second resin layer 12 is disposed on both sides of a first resin layer 11. In the two-layer laminate 10, the innermost layer that comes into contact with the contents may be the first resin layer 11, and the second resin layer 12 may be disposed on the outer side. In the three-layer laminate 20, the innermost layer that comes into contact with the contents may be one second resin layer 12, and the other second resin layer 12 may be disposed on the outer side.

[0020] The second resin layer 12 is mainly composed of polyethylene, polypropylene, or an ethylene-α-olefin copolymer. The second resin layer 12 preferably contains at least one of polyethylene, polypropylene, or an ethylene-α-olefin copolymer, and if two or more types are used, the total content of the second resin layer 12 is preferably, for example, 50 to 100% by weight. When the second resin layers 12 are disposed on both sides of the first resin layer 11, the thickness, composition, etc. of each second resin layer 12 may be the same, or at least one of the thickness, resin grade, blend ratio, etc. may be different.

[0021] When a sterilization temperature of 120° C. or higher is applied, a polypropylene resin having a high melting point may be disposed instead of the polyethylene resin in the second resin layer 12. When the second resin layer 12 contains a polypropylene resin, it is appropriate to have a structure in which an adhesive resin layer 13 that adheres well to both the first resin layer 11 and the second resin layer 12 is provided between them as shown in FIGS. The laminate 30 shown in Fig. 3 has a three-layer structure in which a second resin layer 12 is disposed on one side of a first resin layer 11 via an adhesive resin layer 13. The laminate 40 shown in Fig. 4 has a five-layer structure in which a second resin layer 12 is disposed on both sides of a first resin layer 11 via an adhesive resin layer 13. When adhesive resin layers 13 are disposed on both sides of the first resin layer 11, the thickness, composition, etc. of each adhesive resin layer 13 may be the same, or at least one of the thickness, resin grade, blend ratio, etc. may be different. When second resin layers 12 are disposed on both sides of the first resin layer 11, only the second resin layer 12 on one side may contain a polypropylene-based resin, or a four-layer structure may be formed in which the adhesive resin layer 13 is provided only between the first resin layer 11 and the second resin layer 12 on one side.

[0022] In order to impart physical properties such as flexibility and transparency appropriate for a plastic container, the second resin layer 12 and the adhesive resin layer 13 may be made of a mixture of two or more resins having different physical properties, or may be arranged in two or more layers. For example, two or more second resin layers 12 containing polyethylene, polypropylene, or an ethylene-α-olefin copolymer as a main component may be adjacent to each other. Alternatively, two or more adhesive resin layers 13 may be arranged between the first resin layer 11 and the second resin layer 12.

[0023] As the polyethylene-based resin (polyethylene or ethylene-α-olefin copolymer) used in the second resin layer 12, linear low-density polyethylene (LLDPE) is suitable. LLDPE is usually produced by copolymerizing α-olefins having 4 or more carbon atoms and introducing short-chain branches, resulting in a linear molecular structure with few long-chain branches. Examples of α-olefins copolymerized in LLDPE include 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. In particular, LLDPE polymerized using a single-site catalyst is preferred because it has a narrow molecular weight distribution and excellent mechanical properties. Examples of single-site catalysts include metallocene catalysts. Examples of metallocene catalysts include catalysts containing metallocene compounds that contain a ligand with a cyclopentadienyl skeleton and the metal is zirconium, hafnium, or the like.

[0024] The polypropylene-based resin layer used in the second resin layer 12 is a layer mainly containing a polypropylene (PP)-based resin. The polypropylene-based resin used in the polypropylene-based resin layer may be a homopolymer of propylene or a copolymer with at least one of ethylene or α-olefins having 4 to 8 carbon atoms. When the polypropylene-based resin contained in the polypropylene-based resin layer is a copolymer, the copolymer may be a random copolymer or a block copolymer. The polypropylene-based resin layer may contain one type of polypropylene-based resin, or may contain two or more types of polypropylene-based resin layers. In order to impart flexibility to the polypropylene-based resin layer, a grade of soft polypropylene (R-TPO) may be selected, and rubber or a thermoplastic elastomer component may be added as necessary.

[0025] For example, when a cyclic olefin resin layer and a polypropylene resin layer are bonded to each other, the adhesive resin layer 13 may be a resin layer containing a resin component consisting of linear low-density polyethylene, a styrene elastomer, and a polypropylene resin, and having a weight ratio of (linear low-density polyethylene):(total of styrene elastomer and polypropylene resin) within a range of 40:60 to 95:5. Other examples include Modic (registered trademark), a polyolefin adhesive resin from Mitsubishi Chemical Corporation and MCPP Innovation LLC, and ZELAS (registered trademark), an olefin thermoplastic elastomer.

[0026] The first resin layer 11 may be made of a resin having a cyclic hydrocarbon skeleton (cyclic olefin skeleton) as a unit structure, and having a glass transition temperature sufficiently higher than the storage environment of the contents. The resin constituting the first resin layer 11 is a polymer made of one or more kinds of olefin monomers or a polymer whose double bonds are hydrogenated, and at least one of the olefin monomers is a cyclic olefin monomer having a cyclic hydrocarbon skeleton. Examples of the cyclic olefin monomer include norbornene compounds. Such amorphous polymers are referred to herein as cyclic olefin resins. The cyclic olefin resin may be a copolymer in which at least one of two or more olefin monomers is an acyclic olefin monomer having no cyclic hydrocarbon skeleton. Examples of the acyclic olefin monomer that can be used for the cyclic olefin resin include ethylene and α-olefins having 4 to 8 carbon atoms.

[0027] Cyclic olefin resins include polymers obtained by hydrogenating the remaining double bonds after ring-opening metathesis polymerization of a norbornene compound, addition polymers made of two or more kinds of cyclic olefin monomers, addition polymers obtained by copolymerizing a cyclic olefin monomer and a non-cyclic olefin monomer, etc. Methods for producing cyclic olefin resins include a method of hydrogenating a ring-opening metathesis polymer of a norbornene compound, a method involving a copolymerization reaction of two or more kinds of cyclic olefin monomers, and a method involving a copolymerization reaction of a cyclic olefin monomer and an α-olefin.

[0028] The basic structure of the hydrogenated polymer of the ring-opening metathesis polymer of a norbornene compound is, for example, represented by the following formula (I). That is, the polymer is described in formula (I) as having a cyclic skeleton and an ethylene skeleton arranged alternately. The cyclic skeleton in formula (1) is a 1,3-cyclopentylene skeleton. However, the ring-opening metathesis polymer of a norbornene compound itself does not have to be a copolymer.

[0029] [ka]

[0030] In formula (I), n is an integer of 1 or more, and R 1 and R 2 R represents a hydrogen atom or an alkyl group. 1 and R 2 may be the same or different. 1 and R 2 may be bonded to each other to form a ring.

[0031] The structure shown in formula (I) is a 1,3-cyclopentylene skeleton having n substituents R 1 and R 2 are the same and the ring-opening metathesis polymer of a norbornene compound is not limited to a homopolymer. The structure shown in formula (I) may be a polymer obtained by hydrogenating two or more ring-opening metathesis polymers of a norbornene compound. An example of such a polymer is the following formula (II).

[0032] [ka]

[0033] In formula (II), m and n are integers of 1 or more, and R 1 and R 2 represents a hydrogen atom or an alkyl group. m and n may be the same or different. R 1 and R 2 may be the same or different. 1 and R 2 may be bonded to each other to form a ring.

[0034] Specific examples of the polymer obtained by hydrogenating the ring-opening metathesis polymer of a norbornene compound include "ZEONEX (registered trademark)" and "ZEONOR (registered trademark)" manufactured by Zeon Corporation.

[0035] An example of an addition polymer obtained by copolymerizing a cyclic olefin monomer and a non-cyclic olefin monomer is represented by the following formula (III). The copolymer of formula (III) is described as a polymer in which a cyclic skeleton and an ethylene skeleton are randomly arranged. The cyclic skeleton of formula (I1I) is a 2,3-norbornanylene skeleton.

[0036] [ka]

[0037] In formula (III), m and n are integers of 1 or more, and R 1 , R 2 and R 3 represents a hydrogen atom or an alkyl group. m and n may be the same or different. R 1 , R 2 and R 3 may be the same or different. 1 and R 2 may be bonded to each other to form a ring.

[0038] Here, R 1 , R 2 , R 3 An example of a polymer in which both R are hydrogen atoms is "TOPAS (registered trademark)" manufactured by Polyplastics Co., Ltd. 1 and R 2 is an alkyl group, and R 3 An example of a polymer in which is a hydrogen atom is APEL (registered trademark) manufactured by Mitsui Chemicals, Inc.

[0039] These cyclic olefin resins have excellent water vapor barrier properties and are easily available. As described above, in the laminate of this embodiment, these cyclic olefin resins can be used as the main component of the first resin layer. The first resin layer preferably contains at least one type of cyclic olefin resin, and if two or more types are used, the total amount of the cyclic olefin resins is preferably, for example, 50% by weight or more and less than 100% by weight.

[0040] The first resin layer may contain one kind of cyclic olefin resin, or may contain two or more kinds of cyclic olefin resin. Here, the two or more kinds of cyclic olefin resin may be two or more kinds of cyclic olefin resin corresponding to any one of formulas (I) to (III), may be one or more kinds of cyclic olefin resin for each of two or more formulas (I) to (III), and may further contain a cyclic olefin resin not corresponding to formulas (I) to (III). In addition, the first resin layer may be the innermost layer (sealant layer) in the laminate.

[0041] Next, examples of commercially available cyclic olefin resins are given below. Although some of the above are overlapped, examples include ZEONEX (registered trademark) (manufactured by Zeon Corporation, hydrogenated polymer of ring-opening metathesis polymer of norbornene-based monomer), TOPAS (registered trademark) (manufactured by Polyplastics Corporation, copolymer of norbornene and ethylene), ZEONOR (registered trademark) (manufactured by Zeon Corporation, copolymer based on ring-opening polymerization of dicyclopentadiene and tetracyclopentadodecene), APEL (registered trademark) (manufactured by Mitsui Chemicals, Inc., copolymer of ethylene and tetracyclododecene), and ARTON (registered trademark) (manufactured by JSR Corporation, cyclic olefin resin containing polar groups made from dicyclopentadiene and methacrylic acid ester as raw materials).

[0042] The first resin layer contains an elastomer in addition to the cyclic olefin resin. Examples of the elastomer used in the first resin layer include rubber and thermoplastic elastomer. The first resin layer contains an elastomer, which can reduce the risk of breakage when an external force such as a drop is applied. The ratio of the elastomer contained in the first resin layer is preferably 10% by mass or less, and is desirably between 0.05 and 10% by mass. When the composition ratio of the cyclic olefin resin is low, the risk of breakage when an external force such as a drop is applied is reduced, but trace components and drug components with high affinity to plastics are adsorbed, and the storage stability of the drug components contained therein may be insufficient. The ratio of the cyclic olefin resin contained in the first resin layer is preferably 90% by mass or more, and is desirably between 90 and 99.95% by mass. The first resin layer does not need to contain a non-cyclic polyolefin resin such as PE or PP, and the polymer components contained in the first resin layer may be only the cyclic olefin resin and the elastomer.

[0043] The elastomer used in the first resin layer is preferably a styrene-based elastomer. Examples of the styrene-based elastomer used in the first resin layer include copolymers of styrene and aliphatic olefin. A block containing styrene constitutes a hard block, and a block containing an aliphatic olefin constitutes a soft block. Specific examples of the styrene-based elastomer include one or more of styrene-ethylene copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-isoprene-butadiene-styrene block copolymer (SIBS), styrene-ethylene-butylene-olefin crystalline block copolymer (SEBC), hydrogenated styrene-butadiene rubber (HSBR), etc.

[0044] The elastomer used in the first resin layer may be an olefin-based thermoplastic elastomer. Examples of olefin-based thermoplastic elastomers (sometimes referred to as "TPO") include copolymers having an olefin-based polymer (resin component) such as polyethylene (PE) or polypropylene (PP) as a molecular restraining component (hard segment) and an olefin-based rubber component such as ethylene-propylene-diene terpolymer (EPDM) or ethylene propylene rubber (EPR) as a flexible component (soft segment) exhibiting rubber elasticity.

[0045] The materials constituting each layer constituting the laminate of this embodiment, i.e., the first resin layer, the adhesive resin layer, the second resin layer, etc., may contain various additives such as antioxidants, ultraviolet absorbers, antistatic agents, lubricants, antiblocking agents, etc., within a range that does not impair safety and hygiene, in order to improve the container appearance, stabilize the quality, and impart other required performance.

[0046] The method for forming each layer (film) used in the laminate (sheet) of this embodiment is not particularly limited, and examples thereof include T-die molding, inflation molding, etc. After T-die molding, the film, sheet, etc. may be quenched with a cooling roll. When continuously forming a long film, sheet, etc., it is preferable to wind up the long molded product such as the film, sheet, etc. after molding, as this provides excellent productivity.

[0047] The laminate may be a laminate of a substrate, a sealant layer, and other layers as necessary. That is, an adhesive layer or an anchor layer may be interposed between each layer, or the layers may be laminated so as to be in direct contact with each other. As the other layer, one or more layers such as a reinforcing layer, a gas barrier layer, a light-shielding layer, a printing layer, etc. may be appropriately selected. The sealant layer is a layer used for heat sealing, and is disposed in the innermost layer in contact with the contents as a packaging material. Heat sealing is a method of bonding by melting the sealant layer, but there is no particular restriction on the sealing method, and examples thereof include hot plate sealing, ultrasonic sealing, high frequency sealing, and impulse sealing. The substrate may be the outermost surface of the other side of the laminate opposite to the sealant layer, or may be laminated inside the outermost surface of the other side.

[0048] The method for producing the laminate of this embodiment is not particularly limited, and each layer constituting the laminate may be appropriately laminated by extrusion lamination, dry lamination, co-extrusion, or a combination of two or more of these methods. The thickness of the sealant layer depends on the application of the packaging material and is not particularly limited, but is usually about 5 to 150 μm, preferably 15 to 100 μm. The thickness of the adhesive resin layer is not particularly limited, but is, for example, 10 to 100 μm. The total thickness of the laminate is preferably 150 to 300 μm, and is particularly generally 190 to 250 μm, in view of the balance between the required performance (transparency, flexibility) and cost (productivity, material cost).

[0049] According to the laminate of this embodiment, the interlayer strength between the first resin layer and the second resin layer, or the interlayer strength between the first resin layer, the adhesive resin layer, and the second resin layer can be significantly improved. In the laminate of the present embodiment, when the second resin layer contains a polypropylene resin, the laminate has higher heat resistance than a laminate composed of a polyethylene resin layer and a cyclic olefin resin layer, and therefore has heat resistance even at high temperatures exceeding 120°C and can be sterilized by high-pressure steam. Furthermore, the laminate of the present embodiment has higher heat resistance than a laminate composed of a polypropylene-based resin layer and a cyclic olefin-based resin layer, and even when subjected to high-pressure steam sterilization, the decrease in peel strength is suppressed, and the impact resistance of the container can be improved.

[0050] The container of this embodiment can be formed using the laminate of this embodiment. Examples of the container include packaging bags (pouches), tube packaging, and the like. When providing a spout in the packaging bag, the spout can be suitably used as long as it can be joined to the sealant layer of the laminate constituting the packaging bag to ensure hermeticity. It is preferable to use a spout made of a sealant layer of the laminate and a heat-sealable resin to join the spout and the laminate by heat sealing. When heat sealing the laminate and the spout, the spout may be inserted between the laminates stacked with the sealant layer on the inside and heat sealed, or a flange or a boat-shaped fusion base may be provided at one end of the spout, and the flange or fusion base may be heat sealed to the periphery of a hole provided in the laminate or the inner surface of the opening of the packaging bag.

[0051] The container of the present embodiment can be suitably used as a container for storing medicines such as pharmaceuticals, foods and beverages, cosmetics, etc. The medicine may be a substance having high adsorption or permeability to general resins, such as nitroglycerin, albumin, vitamins, trace elements, radical scavengers, etc. A preferred medicine or other medicine is an aqueous solution containing edaravone, which is a pyrazolone derivative, or a pharma- ceutical acceptable salt thereof. The pyrazolone derivative may have one or more substituents, such as an alkyl group, an aromatic group, or a halogen atom, on the carbon atom or nitrogen atom of the pyrazolone. The pyrazolone derivative may form a salt with an organic acid, an inorganic acid, etc.

[0052] The form of the packaging bag can be applied without any particular limitation to small packaging bags (pouches) such as three-sided bags, four-sided bags, seamed bags, gusset bags, and self-supporting bags, as well as large bags such as inner bags for bag-in-boxes and drum can interior bags. As the form of the container, as shown in Fig. 5, a plastic container 50 having a storage section 51 for storing the contents and an opening section 52 for discharging the contents is preferable, and examples thereof include an infusion bag or a blow molded container. The storage section 51 can be configured by arranging the laminate of this embodiment so as to overlap each other and face each other.

[0053] The present invention has been described above based on a preferred embodiment, but the present invention is not limited to the above-mentioned embodiment, and various modifications are possible without departing from the gist of the present invention. EXAMPLES

[0054] The present invention will now be described in detail with reference to examples.

[0055] (Method of manufacturing laminate) Using a T-die type multilayer film-forming machine, a laminate was produced by a co-extrusion method so that the thicknesses of the surface layer, intermediate layer, and innermost layer were 180 μm, 50 μm, and 30 μm, respectively. The surface layer (second resin layer) is made of a polypropylene-based thermoplastic elastomer "Zelas (registered trademark)" (manufactured by Mitsubishi Chemical Corporation, density 0.89 g / cm 3 , melting peak temperature 162°C) was used.

[0056] For the intermediate layer (adhesive resin layer), pellets were used that were dry-blended in a predetermined ratio with three components consisting of LLDPE, polypropylene (PP), and a compatibilizer. The LLDPE was a gas-phase metallocene polyethylene "Harmolex (registered trademark)" (Japan Polyethylene Corporation, density 0.908 g / cm 3 The PP used was a metallocene-based polypropylene "Wintec (registered trademark)" (manufactured by Japan Polypropylene Corporation, density 0.90 g / cm 3and melting peak temperature 125°C). SEBS "Tuftec (registered trademark)" (manufactured by Asahi Kasei Corporation) with a styrene content of 12% by weight was used as the compatibilizer. The adhesive resin layer was blended in a mass ratio of LLDPE:PP:SEBS=55:35:10.

[0057] The innermost layer (first resin layer) is made of cyclic olefin resin "TOPAS (registered trademark)" (density 1.02 g / cm 3 A 100% elastomer having a glass transition temperature of 138°C was used and various elastomer components shown in Table 1 were blended in the prescribed ratios.

[0058] [Table 1]

[0059] As the four types of SEBS (styrene-ethylene-butylene-styrene block copolymer), "Tuftec (registered trademark)" (manufactured by Asahi Kasei Corporation, styrene content 12 to 43% by weight) was used. As the SEPS (styrene-ethylene-propylene-styrene block copolymer), "Septon (registered trademark)" (manufactured by Kuraray Co., Ltd., styrene content 18% by weight) was used. As the SEBC (styrene-ethylene-butylene-olefin crystalline block copolymer), HSBR (hydrogenated styrene-butadiene rubber), and CEBC (olefin crystalline-ethylene-butylene-olefin crystalline block copolymer), "Dynaron (registered trademark)" (manufactured by JSR Corporation) were used.

[0060] (Experiment 1) Using the above-mentioned laminate manufacturing method, a laminate having an innermost layer with the composition shown in Table 2 was manufactured. The innermost layers of the laminate thus formed were overlapped and the outer periphery of the laminate was heat-sealed except for the filling port to produce an infusion bag-shaped pouch container with outer dimensions of 172 mm x 115 mm. The outer periphery was trimmed to a width of 5 mm, and the pouch was filled with 105 mL of water, and then the filling port was heat-sealed to hermetically seal the pouch.

[0061] [Table 2]

[0062] The sealed pouch was sterilized at high pressure using a high pressure steam sterilizer at 121°C for 20 minutes. After high pressure sterilization, the pouch was cooled quickly with cooling water, and the pouch was subjected to heat seal strength, transparency, and impact resistance in a drop test. In addition, the pouch was filled with a model formulation (described later) instead of water as the content, and the stability of the pouch after long-term storage was evaluated.

[0063] The heat seal strength was measured by the following procedure. First, a test piece with a width of 15.0 mm and an expanded length of 100 mm or more was taken in a direction perpendicular to the heat seal part of the pouch, and the sheet parts on both sides of the heat seal part were opened 180° with the heat seal part of the test piece in the center, and each sheet part on both sides was attached to the grip part of a tensile tester with a grip distance of 50 mm. Next, the tensile load was measured at a constant pulling speed of 300 mm / min until the heat seal part broke, and the maximum load (N / 15 mm) until the break was taken as the heat seal strength. In assessing heat seal strength, taking into consideration JIS Z0238 (test method for heat-sealed flexible packaging bags and semi-rigid containers), a strength of 23N / 15mm or more "when a strong heat seal strength is required, such as for bags for retort sterilization" was rated as "good," and anything less than this was rated as "poor."

[0064] Transparency was evaluated by the following procedure. According to the first transparency test method described in 7.02 Plastic Drug Container Test Methods of the 17th Revised Japanese Pharmacopoeia (JP17), five laminate specimens measuring 0.9 cm x 4 cm were cut out from the pouch and immersed in a cell filled with water for measuring ultraviolet absorption spectrum. Using a cell filled with water only as a control, the light transmittance at a wavelength of 450 nm was measured and recorded using a UV-visible spectrophotometer. Regarding the evaluation of transparency, taking into consideration that the standard for plastic containers for aqueous injections in the Pharmacopoeia requires a light transmittance of 55% or more, a value of "good" was used for the average of the light transmittance measurements of five specimens of 65% or more, and a value of less than this was used for "poor".

[0065] Impact resistance in a drop test was evaluated according to the following procedure. A bag filled with water and sterilized was cooled in a refrigerator at 5°C for at least 12 hours. While kept in a cold state, the bag was dropped from a height of 2m with the pouch facing down, and 50 consecutive drops were performed on each bag. If any cracks were observed in the bag, the test was stopped at that point, the number of drops at which the bag broke was recorded, and a score was assigned based on the following formula:

[0066] (Drop test score) = 0.2 x (number of drops when bag breaks - 1) However, for specimens that did not show any breakage after 50 drops, the number of drops before breakage (number of drops when breakage occurred - 1) was considered to be 50, and the drop test score was given as 10 points.

[0067] For each level, 10 bags were tested, and the total drop test score for the 10 samples was calculated as the total drop test score. The total drop test scores for each level were compared to determine the superiority or inferiority of performance. A drop test score of 80 points or more was rated "good," and one below 80 points was rated "poor."

[0068] The storage stability of the model formulation was evaluated according to the following procedure. From the laminate produced according to the laminate production method described above, a pouch container in the shape of an infusion bag was formed as described above. The container was filled with 105 mL of an edaravone-containing aqueous solution adjusted to pH 3.85 with the composition shown in Table 3 below (composition of edaravone model formulation), and sealed. The container containing the model formulation was sterilized at 121°C for 20 minutes using a high-pressure steam sterilizer, and after cooling, the outside of the container was dried to prepare a bag formulation. The bag formulation that had completed the sterilization process was placed in a dry laminate exterior bag consisting of a three-layer structure of biaxially oriented polyester / aluminum foil / linear low-density polyethylene together with an oxygen scavenger ("Ageless (registered trademark)" manufactured by Mitsubishi Gas Chemical Company, Inc.), and the opening of the exterior bag was heat-sealed to complete the preparation of a bag specimen containing the model formulation.

[0069] [Table 3]

[0070] The prepared bag specimens containing the model formulation were stored for 15 days in an environment of temperature: 70°C and relative humidity: 90%. The residual rate of edaravone after storage was measured by liquid chromatography under the following conditions.

[0071] Detector: Ultraviolet absorption photometer (measurement wavelength: 243 nm) Column: A liquid chromatography column consisting of a stainless steel tube with an inner diameter of 4.6 mm and a length of 150 mm packed with octadecylsilylated silica gel with a particle size of 5 μm. Column temperature: constant temperature around 40°C. Mobile phase: methanol: water: acetic acid = 49.8: 49.8: 0.4 Flow rate: 1.0mL / min. Injection volume: 20μL

[0072] From the test sample bag, exactly 3 mL of the content was taken, which corresponds to about 0.9 mg of edaravone, and the mobile phase was added to make 10 mL. From this liquid, 1 mL was accurately measured, and the mobile phase was added to make exactly 100 mL, which was used as the test solution. 20 μL of the test solution was tested by liquid chromatography under the above test conditions. Each peak area was measured by automatic integration. The remaining rate of the edaravone component was calculated for each test condition using the following formula. The initial peak area of ​​edaravone was measured in the same manner as the peak area of ​​edaravone after the completion of the storage test, after exactly 3 mL was taken from the model formulation immediately after preparation before filling the test sample bag.

[0073] Edaravone remaining rate (%) = (peak area of ​​edaravone after completion of storage test) / (initial peak area of ​​edaravone) × 100 (%)

[0074] When the residual rate of edaravone relative to the initial value was in the range of 95% to 105%, it was judged as "good", and when it deviated from this range it was judged as "poor".

[0075] The results of a series of evaluations are shown in Table 4. It was shown that the inclusion of an elastomer component and an amorphous polymer in the innermost layer (first resin layer) did not cause a decrease in heat seal strength, and significantly improved impact resistance. However, when the amount of elastomer component added was excessive, it was clear that the transparency after sterilization and the storage stability of the model formulation approached insufficient levels, suggesting that a composition containing a certain proportion of the elastomer component is appropriate.

[0076] [Table 4]

[0077] (Experiment 2) In order to verify whether a similar performance improvement effect would be achieved when an elastomer component other than that used in Experiment 1 was added, a laminate was produced having an innermost layer with the elastomer addition amount shown in Table 5. The other procedures (pouch preparation, sterilization treatment, measurement of heat seal strength and transparency, drop test, storage stability of model formulation) were the same as in Experiment 1.

[0078] [Table 5]

[0079] A series of evaluation results in Experiment 2 are shown in Table 6 together with the evaluation results of No. 0 and No. 1-1 in Experiment 1. Significant improvement in impact resistance was achieved regardless of the type of styrene-based elastomer. As shown by No. 2-7, the addition of an olefin-based elastomer component that does not contain a polystyrene block had a lower modifying effect than the addition of a styrene-based elastomer, but it was confirmed that the required performance for a drug solution bag container was met.

[0080] [Table 6]

[0081] (Experiment 3) In order to verify whether a performance improving effect is achieved when the polyolefin resin presented in Patent Document 2 and Patent Document 3 is added instead of the elastomer added to the innermost layer in Experiments 1 and 2, and the amount of addition required to achieve the performance improving effect, a laminate was manufactured with the innermost layer composition of the added resin and the blending amount shown in Table 7. The other procedures (pouch preparation, sterilization treatment, measurement of heat seal strength and transparency, drop test, storage stability of model formulation) were the same as those in Experiments 1 and 2. Of the polyolefin types in Table 7, the same brands of LLDPE and random PP were used as the resin constituting the intermediate layer (adhesive resin layer).

[0082] [Table 7]

[0083] A series of evaluation results in Experiment 3 are shown in Table 8 together with the evaluation results of No. 0 and No. 1-1 in Experiment 1. The blending of polyethylene (LLDPE) did not provide the required performance at the same level of addition as elastomer, and a tendency was observed that a large amount of blending was required to increase impact resistance, as in No. 3-4. The blending of polypropylene (random PP) did not provide sufficient impact resistance even when added up to 20%. On the other hand, when the blending amount was increased, the residual rate of edaravone in the model formulation decreased, suggesting that the performance required for a pharmaceutical storage container cannot be met. In addition, it was confirmed that the blending of polypropylene gradually decreased the heat seal strength after sterilization as its ratio was increased. When polyolefin resin was added to the innermost layer, there was no laminate that fell below the standard for heat seal strength at an addition amount up to 20%, but none that met all the other required performances were found in the series of laminates in Experiment 3.

[0084] [Table 8] [Industrial Applicability]

[0085] According to the present invention, it is possible to provide a laminate and a plastic container which have excellent interlayer adhesive strength and heat seal strength, are resistant to loss of transparency even during high-temperature sterilization treatment and the like, are resistant to breakage due to impacts such as being dropped, have appropriate strength as a storage container, and have excellent storage stability of the ingredients of the contained contents, such as pharmaceuticals. [Explanation of symbols]

[0086] 10, 20, 30, 40...Laminate 11...First resin layer 12…Second resin layer 13…Adhesive resin layer

Claims

1. a first resin layer including an amorphous cyclic olefin-based resin composed of an olefin monomer component having a cyclic hydrocarbon skeleton; A laminate consisting of at least two layers, including a second resin layer mainly composed of polyethylene, polypropylene or an ethylene-α-olefin copolymer, The first resin layer contains a thermoplastic elastomer in an amount of 10% by mass or less and is an innermost layer that comes into contact with the contents; A laminate in which an adhesive layer or an anchor agent layer may be provided between each of the layers.

2. 2. The laminate according to claim 1, wherein the thermoplastic elastomer is at least one selected from the group consisting of olefin-based thermoplastic elastomers and styrene-based thermoplastic elastomers.

3. 3. The laminate according to claim 1, wherein the thermoplastic elastomer is contained in the first resin layer in an amount of 0.05 to 10% by mass.

4. A plastic container comprising a storage section for storing contents and an opening for discharging the contents, the storage section being arranged so that the laminate according to any one of claims 1 to 3 is overlapped and facing each other.

5. 5. The plastic container according to claim 4, wherein the contents are medicines.

6. 6. The plastic container according to claim 5, wherein the pharmaceutical is an aqueous solution containing edaravone, a pyrazolone derivative, or a pharma- ceutically acceptable salt thereof.

7. The plastic container according to any one of claims 4 to 6, which is an infusion bag or a blow molded container.

Citation Information

Patent Citations

  • Multilayer film and drug container using the same

    JP2005525952A

  • Package

    JP2010162344A

  • Plastic container comprising cyclic polyolefin layer

    JP2011062529A

  • Laminated film, and packaging container using the laminated film

    JP2011230322A

  • Laminated film, and packaging container using the laminated film

    JP2011230380A

Cited By

  • Laminate and plastic container

    JP2023066723A

  • Laminate and plastic container

    JP7753055B2